2018
DOI: 10.14527/pegegog.2019.006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between teachers' perceptions of organizational justice and job satisfaction

Abstract: The purpose of this research is to determine the relationship between teachers’ perceived organizational justice and job satisfaction. This quantitative study is designed in relational survey model. The sample of the research consists of 396 teachers working in the public high schools located in four central provinces of Mersin city. Organizational Justice Scale and Job Satisfaction Scale were used as data collection tools in the study. Arithmetic mean, standard deviation, t test, ANOVA and correlation analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…Overall, rather than the actual retention or attrition rate, most studies on this topic mention teachers' perspectives and intentions to leave (e.g. Alanoğlu and Demirtaş, 2018; Mérida-López and Extremera, 2020). Besides the common influencing factors like workplace condition, climate and student achievement, there are also several studies about teachers' overall impact on society (Cek and Eyupoglu, 2019) and pre-service teachers (Eren, 2017).…”
Section: Conceptual Structure and Intellectual Structure Of Studies O...mentioning
confidence: 99%
“…Overall, rather than the actual retention or attrition rate, most studies on this topic mention teachers' perspectives and intentions to leave (e.g. Alanoğlu and Demirtaş, 2018; Mérida-López and Extremera, 2020). Besides the common influencing factors like workplace condition, climate and student achievement, there are also several studies about teachers' overall impact on society (Cek and Eyupoglu, 2019) and pre-service teachers (Eren, 2017).…”
Section: Conceptual Structure and Intellectual Structure Of Studies O...mentioning
confidence: 99%
“…When teachers hold positive perceptions of their schools, it is expected that they will work more happily and achieve greater success (Alanoğlu, 2019). Conversely, in the absence of positive perceptions, a decline in teachers' trust, a lack of engagement in their work, and ultimately, a decrease in their commitment and performance within the institutions may occur (Uysal, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, research by Öztürk (2020) suggests that teachers' organizational justice perceptions are low. Some studies have reported a significant negative relationship between teachers' perceptions of organizational justice and various factors, such as emotional exhaustion (Alanoğlu, 2019) and organizational hypocrisy (Kahveci et al, 2019). In contrast, a positive significant relationship has been observed between teachers' perceptions of organizational trust and justice and their perceptions of an enabling school structure (Arik, 2021), job satisfaction (Altınkurt & Yılmaz, 2012), organizational trust (Polat & Celep, 2008), organizational citizenship behaviors (Rauf, 2014), organizational commitment (Jameel et al, 2020), teacher performance (Chandrawaty & Widodo, 2021), school climate, teacher professionalism, leadership style, academic achievement, community engagement, reliance on principals, colleagues, and clients (Dipaola & Guy, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations